Incidence of intersex in male clams Scrobicularia plana in the Guadiana Estuary (Portugal) - Gomes, Tânia (2020)
Endocrine disrupting chemicals (EDCs) known to be present in the marine environment, have great potential to influence reproductive status in aquatic organisms. A widespread incidence of intersex linked with EDCs exposure has been reported in molluscs and fish species. The species Scrobicularia plana is inherently gonochoristic; nonetheless, the feminisation of male clams was described in estuaries from the United Kingdom. Thus, this study reports the presence of oocytes in the testis of male clams of S. plana collected in the Guadiana River (Portugal). Samples were collected between June and September (2007), and gonad tissue analysed by light microscopy. Intersex with several degrees of intensity was detected during the first three months of sampling, in which the percentage of male clams affected varied between 5.9, 58.3 and 71.4%. Little is known about the causes of intersex in S. plana, being the urban, industrial and agricultural discharges possible major sources of induction. In the Guadiana River, the presence of several EDCs may be directly linked to the incidence of the intersex condition detected in Scrobicularia plana.